Pengembangan LKPD Berbasis PBL Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP Negeri 1 Tanjung Morawa - Saragih, Agnes Liska Rosadani; Hasratuddin Hasratuddin (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The purpose of this research was to produce a worksheet based on problem-based learning that would enhance students' ability to communicate mathematically when working with number pattern content. The quality of this LKPD refers to the effective aspect. This research uses a type of research and development (R&D) with a model developed by Borg & Gall. The subjects in this research were students in class VIII-5 of SMP Negeri 1 Tanjung Morawa with a total of 27 students. The object of this research is teaching materials in the form of PBL-based LKPD. Teacher response questionnaires, student response questionnaires, expert validation sheets, teacher interview question sheets, and tests of mathematical communication competence were the tools employed. Based on the research results, the effectiveness of LKPD can be seen from the achievement of learning completeness with an average individual learning completeness of 88 and for classical completeness of 96.3%. So the LKPD developed is declared "effective". Students' mathematical communication abilities are at a percentage of 90.1%, at high criteria, and it can be noted that for the N-Gain assessment, results were obtained with a student average of 0.74, meaning that there was an increase in students' mathematical communication abilities with high criteria. So, based on the results, it can be concluded that the LKPD developed in this research is valid, effective, and can improve students' mathematical communication skills.